ROLE OF SPIRITUALITY AND WELLNESS PRACTICES ON COMPLIANCE WITH COVID-19 PANDEMIC PREVENTIVE MEASURES AMONG HEALTHCARE WORKERS IN OWERRI, NIGERIA - Nnamdi-Annorzie, Helen Ihuoma (African Journal of Social and Behavioural Sciences, 2023)
The study examined the role of spirituality and wellness practices on compliance with pandemic preventive measures among healthcare workers in Owerri, Imo State, Nigeria. Two hundred and fifty healthcare workers comprising 84 males and 166 females drawn from seven health centres in Owerri participated in the study. Their ages ranged from 23 to 49 years with a mean age of 29.71 years and a standard deviation of 6.02 years. Three instruments namely the Religious Affiliation Scale by Omoluabi (1995), the Wellness Inventory by Muokwe (2010), and the Compliance to Pandemic Commands Scale (COCOS) by Morales-vives, et al. (2021) were used. The study adopted a cross-sectional survey design while Hierarchical Multiple Regression was used for analysis. Two hypotheses were postulated and tested. Results revealed that higher levels of spirituality and engaging in wellness practices are substantial predictors of compliance with COVID-19 protocols. The study recommends that changes in health centres be made to prioritize spirituality and the practice of wellness among physicians, nurses, and other healthcare workers to avoid going through a circle of panic and neglect whenever there’s a pandemic or sudden outbreak of diseases.